2022
DOI: 10.1016/j.nicl.2022.102936
|View full text |Cite
|
Sign up to set email alerts
|

Task-induced subjective fatigue and resting-state striatal connectivity following traumatic brain injury

Abstract: Highlights Fatigue is a very frequent and disabling symptom in traumatic brain injury (TBI). Effects of task-induced fatigue on resting-state functional connectivity (rsFC). Striatal rsFC relates differently to subjective fatigue in TBI compared to controls. Default mode network rsFC relates similar to subjective fatigue in TBI and controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Cognitive fatigue is one of the most reported symptoms following TBI ( Beaulieu-Bonneau and Ouellet, 2017 ). Recently, Bruijel et al found that cognitive fatigue was linked to DMN connectivity and was differently associated with striatal connectivity in moderate-severe TBI patients relative to healthy controls ( Bruijel et al, 2022 ). This highlights the dynamic nature of DMN and suggests how changes in one brain area may trigger compensatory neural responses in other brain areas to achieve homeostasis of neural information exchange ( Andrews-Hanna et al, 2010 ).…”
Section: Advanced Magnetic Resonance Imaging Based Techniquesmentioning
confidence: 99%
“…Cognitive fatigue is one of the most reported symptoms following TBI ( Beaulieu-Bonneau and Ouellet, 2017 ). Recently, Bruijel et al found that cognitive fatigue was linked to DMN connectivity and was differently associated with striatal connectivity in moderate-severe TBI patients relative to healthy controls ( Bruijel et al, 2022 ). This highlights the dynamic nature of DMN and suggests how changes in one brain area may trigger compensatory neural responses in other brain areas to achieve homeostasis of neural information exchange ( Andrews-Hanna et al, 2010 ).…”
Section: Advanced Magnetic Resonance Imaging Based Techniquesmentioning
confidence: 99%
“…Interestingly, connectivity of the precuneus with thalamic/striatal areas was also modulated with memory-related performance in an auditory task (Paced Auditory Serial Addition Test; PASAT—see (Boissoneault et al, 2018 ). Additionally, the precuneus was also highlighted as involved in mental fatigue in the previously-discussed studies in different cognitive tasks (Wylie et al, 2017a ; Bruijel et al, 2022 ). Overall, given the strong memory aspect of the visual search task in the present study, the involvement of the precuneus seems well-founded.…”
Section: Discussionmentioning
confidence: 83%
“…As can be seen in the Supplementary Table, there is high variability across rsfMRI studies in terms of acquisition of rsfMRI data with eyes open (e.g., Shumskaya et al, 2017 , Konstantinou et al, 2019 ), eyes fixated on a crosshair (e.g., Bruijel et al, 2022 , Grossner et al, 2019 ), or eyes closed (e.g., Lancaster et al, 2019 ; Threlkeld et al, 2018 ). Although these conditions produce comparable FC results, several studies have shown that acquiring rsfMRI data with eyes fixated on a cross may reduce variability (more control of eye movements), show greater reliability of within-network connections ( Patriat et al, 2013 , Zou et al, 2015 ), and show more significant correlations with demographic and behavioral variables ( Agcaoglu et al, 2019 ).…”
Section: Part 2: Recommendationsmentioning
confidence: 99%